The Analysis of Determinant Factors of Chronic Energy Deficiency (CED) in Pregnant Women With Modification of Lawrence Green and Snehandu B. Kar’s Theories - Siska Yuni Fitria; Suhartini Suhartini; Ristya Widi Endah Yani (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
Throughout the world, almost every day, 800 mothers die due to complications of pregnancy and childbirth, and more than 5 million babies die every year. One factor that can increase the risk of maternal and infant death is Chronic Energy Deficiency (CED) during pregnancy. This research aimed to analyse the determinants of CED factors in pregnant women with modifications to Lawrence Green's and Snehandu B. Kar's theories. This research used an analytical survey with a cross-sectional approach. In August–September 2023, there were 97 cases and 97 controls. The sampling technique was purposive sampling—bivariate analysis used chi-square and multivariate with a logistic regression test. The statistical analysis showed that education, gravida, parity, pregnancy interval, and husband's support have a significant relationship with CED (p<0.05). Meanwhile, age, knowledge, occupation, Antenatal care (ANC) examination, intention to become pregnant, independence in making health decisions, the role of health workers, family and health cadre support, transportation facilities, and ease of obtaining health information were not significant relationships to CED (p>0.05). Multivariate statistical analysis showed primigravida was the most dominant factor (p<0.05). The factors of education, gravida, parity, pregnancy interval, and husband's support were significant relationships with CED in pregnant women. The most dominant factor causing CED is primigravida. We recommend providing optimal FE tablets and educating adolescents about the importance of adolescent nutrition and integrated services in the school environment.